223 THE ROLE OF SARS-COV-2 VACCINATION-INDUCED MYOCARDITIS IN UNMASKING UNDERLYING ARRHYTHMOGENIC CARDIOMYOPATHIES: A CASE SERIES LOOKING BEYOND THE TIP OF THE ICEBERG. (15th December 2022) - Brusamolino, Matteo; Amelotti, Nicola; Mapelli, Massimo; Baggiano, Andrea; Campodonico, Jeness; Majocchi, Benedetta; Ribatti, Valentina; Vettor, Giulia; Teruzzi, Giovanni; Trabattoni, Daniela; Novelli, Valeria; Catto, Valentina; et al.
Abstract: Background: Acute myocarditis (AM) is a heart inflammatory disease that may also rarely occur as a complication of COVID-19 vaccines. Inflammation is involved in arrhythmogenic cardiomyopathy (ACM) pathogenesis. Little is known regarding the COVID-19 vaccines influence on ACM relapses. We present two cases of vaccine related AM revealing a pre-existent (silent) ACM. Cases presentation: Table shows a summary of the patients' main clinical characteristics. Discussion: We presented 2 cases of arrhythmic myocarditis-like clinical presentation in patients without previous cardiovascular history, whose timing was temporally related to a dose of vaccine against COVID-19. Subsequent diagnostic workup suggested the possible presence of an underlying silent ACM. In our case series, tissue characterization provided by CMR played a fundamental role as a diagnostic tool, showing in all cases a prominent left ventricle involvement and identifying both the underlying ACM disease and the superimposed myocardial inflammation. We hypothesize that a vaccine-induced AM could have revealed the presence of a pre-existent ACM, on which an inflammatory acute phase triggered the arrhythmic manifestation. Conclusion: Vaccine-induced AM could reveal the presence of a pre-existent ACM. Our report suggests that a high index of suspicion and a multidisciplinary approach is required, in order to continue the diagnostic process once the acute event has been resolved, as it may have fundamental implication in the patient management. Further studies are required to verify if some of the vaccine-triggered AM represent the ACM first manifestation.